Tanggung Jawab Nakhoda KM Sabuk Nusantara 62 Atas Kerusakan Terumbu Karang di Pulau Mius Mangara Kabupaten Raja Ampat - Fijkar Wailisaholong; Ani Wijayati; Gindo L. Tobing (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
This research was conducted to know and analyze related to the captain's responsibility for the sinking of KM Belt Nusantara 62 and the settlement of coral reefs/compensation from the perspective of the Minister of Marine Affairs and Fisheries Regulation Number 28 of 2020 concerning Procedures for Dispute Resolution in the Management of Coastal Areas and Small Islands. This study also uses qualitative research methods with a normative approach where researchers conduct case studies (Case Research), data obtained by researchers related to events through shipping court decisions number: HK.212/05/IV/MP.2022 regarding KM ship accidents. Nusantara Belt 62 in the waters west of Yefmi island and the waters of Gag island in Raja Ampat. Based on data exposure and analysis, the results of the study can be concluded as follows, namely: 1) There are 3 forms of accountability of the Nahkoda KM Belt Nusantara for damage to coral reefs and 2) based on the Regulation of the Minister of Marine Affairs and Fisheries Number 28 of 2020 concerning Procedures for Dispute Resolution in the Management of Coastal Areas and Small Islands, compensation for KM Belt Nusantara 62 can be made through litigation (court) and non-litigation (outside the court).